Follow-up action by the Rethinking Impact Workshop participants and organizers - CGIAR Institutional Learning and Change Initiative; CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation; International Livestock Research Institute (2008)
The Rethinking Impact Workshop (RIW): Understanding the complexity of poverty and change was held in Cali, Colombia, March 26–28, 2008. The workshop discussed (1) how agricultural and natural-resources research can be more effective in contributing to solutions for poverty alleviation and improving gender, social inclusion and equity; (2) how its impact can be assessed; and (3) how such research and impact assessment can be brought into the mainstream. An open-space session was held on the third and fi nal day of the workshop to enable participants to organize themselves into groups for action-planning purposes. Nine action-planning groups were: Principles and standards; Networking and community of practice; Methodologies guidelines (including ‘soft’); Institutionalization; Ex-ante impact assessment, priority-setting and planning; Organizing framework; Capacity-building; Communications; and, Histories and political economy of agricultural and natural-resources science and technology. This Brief reports some of the follow-up actions that the participants and organizers (ILAC Initiative, PRGA Program and ILRI’s Innovation Works) committed themselves to undertaking.